Understanding the Stabilization of a Bulk Nanobubble: A Molecular Dynamics Analysis - Gao, Zhan; Wu, Wangxia; Sun, Weitao; Wang, Bing (Langmuir, 2021)
Bulk nanobubbles (NBs) have received considerable attention because of their extensive potential applications, such as in ultrasound imaging and water management. Although multiple types of experimental evidence have supported the existence and stabilization of bulk NBs, the underlying mechanism remains unclear. This study numerically investigates the bulk NB stabilization with molecular dynamics (MD) methods: the all-atom (AA) MD simulation is used for NBs of several nanometers diameter; the coarse-grained (CG) MD simulation is for the NBs of about 100 nm. The NB properties are statistically obtained and analyzed, including the inner density, inner pressure, surface charge, interfacial hydrogen bond (HB), and gaseous diffusion. The results show that the gas inside an NB has ultrahigh density (tens of kilograms per cubic meter). A double-layer surface charge exists on the NB. The inner/outer layer is positively/negatively charged, and the electrostatic stress can counteract part of the surface tension. In addition, the interfacial HB is weakened by the interaction between gas and water molecules, causing less surface tension. The above features are beneficial to NB stabilization. The NB equilibrium radii solved by the interfacial mechanical equilibrium equation agree with the MD results, indicating that this equation can describe the force balance of an NB as small as several nanometers. Besides, supersaturation appears to be necessary for the NB thermodynamic equilibrium. Based on Henry’s law and the ideal gas law, the theoretical analysis suggests that the stability of the NB thermodynamic equilibrium is conditional: the number of gas molecules in NBs should be more than half that dissolved in liquid. This study unravels a stabilized bulk NB’s properties and discusses the NB equilibrium and stabilization mechanism, which will advance the understanding and application of bulk NBs.